Middleware platform for customizable vehicle reconfiguration - Lim, PC; Wang, YC; Kulathuramaiyer, N (Centre for Academic Information Services, UNIMAS, 2007)
Although the automotive industry is relatively efficient in managing the production line, mass customization remains a major challenge. The difficulty lies in the establishment of channels to support customer feedback and interaction in directing the planning and design new products. There is thus a big gap between user requirements and product features. We explore the development of a platform for bridging this" semantic gap" between user needs and the decision-making process new product planners and designers. This ...